Bioreactor Expansion Reconfigures Metabolism and Extracellular Vesicle Biogenesis of Human Adipose-derived Stem Cells In Vitro - Jeske, Richard (Biochemical engineering journal, 2022)
Human mesenchymal stem cells (hMSCs), including human adipose tissue-derived stem cells (hASCs), as well as the secreted extracellular vesicles (EVs), are promising therapeutics in treating inflammatory and neural degenerative diseases. However, prolonged expansion can lead to cellular senescence characterized by a gradual loss of self-renewal ability while altering secretome composition and EV generation. Additionally, hMSCs are highly sensitive to biophysical microenvironment in bioreactor systems utilized in scaling production. In this study, hASCs grown on Plastic Plus or Synthemax II microcarriers in a spinner flask bioreactor (SFB) system were compared to traditional 2D culture. The SFB microenvironment was found to increase the expression of genes associated with hASC stemness, nicotinamide adenine dinucleotide (NAD+) metabolism, glycolysis, and the pentose phosphate pathway as well as alter cytokine secretion (e.g., PGE2 and CXCL10). Elevated reactive oxidative species levels in hASCs of SFB culture were observed without increasing rates of cellular senescence. Expression levels of Sirtuins responsible for preventing cellular senescence through anti-oxidant and DNA repair mechanisms were also elevated in SFB cultures. In particular, the EV biogenesis genes were significantly upregulated (3-10 fold) and the EV production increased 40% per cell in SFB cultures of hASCs. This study provides advanced understanding of hASC sensitivity to the bioreactor microenvironment for EV production and bio-manufacturing towards the applications in treating inflammatory and neural degenerative diseases